Machine‐to‐machine communications via airliners†. Issue 4 (16th January 2013) - Plass, Simon; Berioli, Matteo; Hermenier, Romain; Liva, Gianluigi; Munari, Andrea; Antón‐Haro, Carles; Lestable, Thierry; Lin, Yonghua; Nikaein, Navid; Watteyne, Thomas; Alonso‐Zarate, Jesus
ABSTRACT Within this article, a new concept for machine‐to‐machine communications infrastructure via airliners is presented. The main principles and resulting challenges are described, together with a first study on possible coverage within Europe and North America using airliners that endorses the concept's feasibility. Accurate insights are drawn by taking into account all commercial flights during 24 h on the basis of real global flight data. We strengthen the proposed solution by investigating system dimension aspects in a proof‐of‐principle manner as well as by discussing medium access policies and coding strategies capable of achieving performance improvements over alternative architectures. The goal of the article is to stimulate further research activities and ideas in this area. Copyright © 2013 John Wiley & Sons, Ltd.